2018
DOI: 10.1111/ibi.12575
|View full text |Cite
|
Sign up to set email alerts
|

Azure‐winged Magpies Cyanopica cyanus trade off reproductive success and parental care by establishing a size hierarchy among nestlings

Abstract: It is common in birds that the sizes of nestlings vary greatly when multiple young are produced in one nest. However, the methods used by parents to establish size hierarchy among nestlings and their effect on parental provisioning pattern may differ between species. In the Azure‐winged Magpie Cyanopica cyanus, we explored how and why parents controlled the sizes of nestlings. Asynchronous hatching was the main cause of size hierarchy within the brood, although the laying of larger eggs later in the laying seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…An inability to discriminate their own offspring from unrelated young may explain this counter-intuitive response of cuckolded males and females. Our cross-fostering experiments in the Tibetan population of the azure-winged magpie show that foster parents do not eject fostered chicks when those fostered chicks are younger than 11-12 d (Da et al 2018). This finding is opposite to the report from the Iberian azure-winged magpies where breeders can reject nearly one half of conspecific eggs (Avilés 2004).…”
Section: No Offspring Discrimination In the Tibetan Azure-winged Magpiesmentioning
confidence: 73%
“…An inability to discriminate their own offspring from unrelated young may explain this counter-intuitive response of cuckolded males and females. Our cross-fostering experiments in the Tibetan population of the azure-winged magpie show that foster parents do not eject fostered chicks when those fostered chicks are younger than 11-12 d (Da et al 2018). This finding is opposite to the report from the Iberian azure-winged magpies where breeders can reject nearly one half of conspecific eggs (Avilés 2004).…”
Section: No Offspring Discrimination In the Tibetan Azure-winged Magpiesmentioning
confidence: 73%
“…Nevertheless, from the perspective of cognitive psychology, the results showed that the magpies have the ability of training transfer and analogical problem solving. The performance of the Azure-winged magpies in string-pulling tasks 24 , 27 and mirror tasks 28 also showed that they have a certain, although limited, spatial cognitive ability. We should emphasize that interference among experiments should be avoided in designing experiments to test cognitive ability.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it is understandable that parents make no reaction to the change of incubation days during the egg phase ( Table 2 ), but significantly respond to the change of nestling ages during the nestling phase ( Table 3 ). In a previous study on the Tibetan azure-winged magpie that involved a cross-fostering experiment, parents began to reject a foreign nestling after it was 10 days old ( Da et al. 2018 ), indicating that parents can recognize their offspring from unrelated nestlings based on the phenotypic traits of nestlings.…”
Section: Discussionmentioning
confidence: 99%
“…2005 ) or the great spotted cuckoo Clamator glandarius ( Soler et al. 2003 ), no cases of nest parasitism by cuckoos have occurred in the Tibetan population ( Da et al. 2018 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation